Uno de los más audaces innovadores en la historia del pensamiento humano (pp. 11-22). Trad. de Enrique Bocardo. - Berlin, Isaiah (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 9-10 (1998). 498 págs. ISBN 1130-7498